Effect of powder concentration on EDM performance during machining mild steel - Khan, Ahsan Ali; Wahid Azmi, Nurfarah; Odenan, Mohd Azim; Mohd Zain, Zakaria (Trans Tech Publications, Switzerland, 2015)
This research work describes the effect of powder concentration in dielectric fluid during electrical discharge machining (EDM) of mild steel on material removal rate (MRR), electrode wear rate (EWR) and work surface roughness (Ra). The machining parameters studied in this research are current (4.5A, 5.5A, and 6.5A) and concentration of the powder (30g/l, 60g/l, and 90g/l). It was decided to use copper (Cu) as the electrode, mild steel as the work material and tantalum carbide (TaC) as the powder to be mixed with the dielectric. Design-Expert software was used to design and analyze the experiments. The performance of machining was analyzed and it was found that powder concentration does not have much effect on MRR or work surface roughness (Ra). At low current powder concentration reduces electrode wear rate (EWR), but at higher current the situation is opposite. It was also found that in all conditions, MRR and EWR increases with increase in current. A higher current produces stronger spark with higher energy that melts more materials from the workpiece and the electrode. As a result both MRR and EWR increases and job surface becomes poor.